2016
DOI: 10.1111/ajag.12264
|View full text |Cite
|
Sign up to set email alerts
|

Facing the times: A young onset dementia support group: FacebookTM style

Abstract: Young onset dementia accounts for up to 1 in 10 dementia diagnoses. Those diagnosed face premature transition into the realm of aged care services and adjustment to an illness of ageing prior to age 65. To help elicit communication of the perceived psychosocial needs of this group, provide a platform to gain peer support and advocate for increased awareness, the Young Onset Dementia Support Group was established on the social networking site, Facebook™ . Followers post comments, read educational or otherwise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…Twenty articles were included, 10 of which were primary studies (Beattie, DakerWhite, Gilliard, & Means, 2004;Carone, Tischler, & Dening, 2016;Hewitt, Watts, Hussey, Power, & Williams, 2013;Kelly & Innes, 2016;Kinney, Kart, & Reddecliff, 2011;O'Connell et al, 2014;Parahoo, Campbell, & Scoltock, 2002;Perkins & Poynton, 1990;Reed, Cantley, Clarke, & Stanley, 2002;Robertson & Evans, 2015). Ten were descriptive accounts of interventions (Barker & Johnson, 2008;Chaston, Pollard, & Jubb, 2004;Craig & Strivens, 2016;Davies-Quarrell et al, 2010;LaFontaine, 2004;Parkes & Ward, 2015;Ramluggun & Ogo, 2016;J. Robertson, Evans, & Horsnell, 2013;Tonga, Arnevik, Werheid, & Ulstein, 2016;Wheeler et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty articles were included, 10 of which were primary studies (Beattie, DakerWhite, Gilliard, & Means, 2004;Carone, Tischler, & Dening, 2016;Hewitt, Watts, Hussey, Power, & Williams, 2013;Kelly & Innes, 2016;Kinney, Kart, & Reddecliff, 2011;O'Connell et al, 2014;Parahoo, Campbell, & Scoltock, 2002;Perkins & Poynton, 1990;Reed, Cantley, Clarke, & Stanley, 2002;Robertson & Evans, 2015). Ten were descriptive accounts of interventions (Barker & Johnson, 2008;Chaston, Pollard, & Jubb, 2004;Craig & Strivens, 2016;Davies-Quarrell et al, 2010;LaFontaine, 2004;Parkes & Ward, 2015;Ramluggun & Ogo, 2016;J. Robertson, Evans, & Horsnell, 2013;Tonga, Arnevik, Werheid, & Ulstein, 2016;Wheeler et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Robertson et al, 2013) and on-line support groups (Craig & Strivens, 2016;O'Connell et al, 2014). Day centres provided activities facilitated by trained staff for a number of hours per week (Beattie et al, 2004), whilst domiciliary respite services were designed to support caregivers, enabling families to keep people living with YOD in their own homes for longer (Parahoo et al, 2002).…”
Section: Types Of Services/interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated value for these types of networks. 38,39 Similarly, individuals with certain personality types (e.g., extroverted versus introverted) might derive more or less benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, social media sites encourage health consumers to communicate and share knowledge directly with one another, fostering interaction, participation, engagement, and community. This is especially visible in the use of social media for support for and education about health-related ailments and concerns [5456]. As social media sites promote the creation of user-generated content, they blur boundaries between producers and consumers of online health-related information.…”
Section: Assessing Reliability On Social Media Sites: Present Contextsmentioning
confidence: 99%